Protein modification in the post-mating spermatophore of the signal crayfish Pacifastacus leniusculus: insight into the tyrosine phosphorylation in a non-motile spermatozoon - Niksirat, Hamid; Vancová, Marie; Andersson, Liselotte; James, Peter; Kouba, Antonín; Kozák, Pavel (Animal reproduction science, 2016)
After mating, spermatophores of signal crayfish are stored on the body of the female for a period before fertilization. This study compared the post-mating protein profile and pattern of protein tyrosine phosphorylation of the signal crayfish spermatophore to that of the freshly ejaculated spermatophore and found substantial differences. Two major bands of tyrosine-phosphorylated proteins of molecular weights 10 and 50kDa were observed in the freshly ejaculated spermatophore of the signal crayfish. While the tyrosine-phosphorylated protein band with molecular weight 10kDa was formed by protein(s) of similar pH, the band with molecular weight of 50kDa consisted of proteins of varying pH. In the post-mating spermatophore, the band with molecular weight of 50kDa was not detected, and an increase in the level of protein tyrosine phosphorylation was observed in the 10kDa band. The microtubular radial arms of the spermatozoon showed a positive reaction to an anti-tyrosine antibody conjugated with gold particles in both the freshly ejaculated and post-mating spermatophores. In conclusion, the male gamete of the signal crayfish undergoes molecular modification during post-mating storage on the body of the female including changes in the level of protein expression and protein tyrosine phosphorylation. Structural similarity of the radial arms in the crayfish immotile spermatozoon with flagellum, which is the main site of protein tyrosine phosphorylation in the mammalian motile spermatozoa, raises questions regarding evolution and function of such organelles across the animal kingdom that must be addressed in the future studies.
Keywords: spermatogonie; proteiny; Male; Sperm Motility; fosforylace; Phosphorylation; Spermatozoa; mužské pohlaví; kopulace; Spermatogonia; tyrosin; Animals; ženské pohlaví; Copulation; zvířata; motilita spermií; Tyrosine; severní raci; spermie; Female; Proteins; Astacoidea